Load frequency control of power systems with renewable energy sources - Yan, Huan (Nanyang Technological University, 2021)
With the rapid development of human society, the demand for energy is increasing rapidly. However, while developing the society and world, the large consumptions of traditional fossil-based energy has produced a huge amount of carbon dioxide which causes climate change. What’s worse, traditional energy will run out in few decades. When compared to traditional energy, renewable energy is a new trend and necessity to develop and build in future. In the application of electric energy, wind energy has also been rapidly developed. Wind energy is kind of clean energy source which is sustainable and cost-effective. Thus, we need to spend more time in studying and developing wind energy. This project is designed to use wind energy to generate power and control load frequency. In order to achieve a stable power generation and system frequency, this report is using MATLAB to simulate the real situation of wind power generation. In this design, firstly, the frequency model of a power system which has a high penetration rate by using renewable energy is given, and the droop control algorithm is used to control the frequency load, and the application of the generator structure and the corresponding control strategy are studied, and its dynamic performance is studied. The structure is flexible, reliable and easy to expand. Simulation and experimental results show that the structure and the corresponding control strategy can stabilize the bus frequency and improve the dynamic performance of wind energy and load change.